2021
DOI: 10.3389/fvets.2021.597964
|View full text |Cite
|
Sign up to set email alerts
|

Rescue and Conservation of Male Adult Alpacas (Vicugna pacos) Based on Spermatogonial Stem Cell Biotechnology Using Atomized Black Maca as a Supplement of Cryopreservation Medium

Abstract: This is the first time that testicular tissue (n = 44) and isolated testicular cells (n = 51) were cryopreserved from alpaca testes 24 h postmortem. For this purpose, internally designed freezing media and cryopreservation protocols were used. Testicular tissue fragments (25 mg) and isolated testicular cells were frozen in MTDB (trehalose and black maca), MTD (trehalose), MSDB (sucrose and black maca), and MSD (sucrose) media. Isolated spermatogonial cells were cryopreserved in two ways, before and after proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…Our data show that the addition of maca (20 mg/mL) to the freezing medium improves motility, viability, and plasma membrane integrity after thawing. In agreement, other studies have demonstrated that the supplementation of the freezing medium with black maca enhanced survival associated with optimized mitochondrial activity of spermatogonial stem cells of alpaca species [48]. Although we did not find differences in the rate of DNA fragmentation between the groups, there was a trend towards a higher rate in the cryopreserved samples.…”
Section: Discussionsupporting
confidence: 91%
“…Our data show that the addition of maca (20 mg/mL) to the freezing medium improves motility, viability, and plasma membrane integrity after thawing. In agreement, other studies have demonstrated that the supplementation of the freezing medium with black maca enhanced survival associated with optimized mitochondrial activity of spermatogonial stem cells of alpaca species [48]. Although we did not find differences in the rate of DNA fragmentation between the groups, there was a trend towards a higher rate in the cryopreserved samples.…”
Section: Discussionsupporting
confidence: 91%
“…All of these options have been summarized in a recent review [ 125 ]. With a view to conservation, some of the techniques have been applied to non-human mammalian [ 126 , 127 , 128 , 129 , 130 ] and avian species [ 131 , 132 ], as well as fishes.…”
Section: Stem Cells Conservation and Ethicsmentioning
confidence: 99%